Photochemical Surface Modification of Titanium Dioxide Nanotube-Coated Surfaces by Ag-Hydroxyapatite Compositions - Khaled Rashwan; Jevin Meyerink; Grigoriy Sereda; Grant Crawford (Journal of Chemistry)
Silver-hydroxyapatite coatings prepared from Ag3PO4 microcrystals have been deposited on titanium dioxide nanotubes supported by titanium disks by photodecomposition of predeposited Ag3PO4 microcrystals or their coprecipitate with hydroxyapatite. The SEM-EDS characterization has confirmed excellent film uniformity and consistent deposition over the surface, which is essential for improving osseointegration of tunable antibacterial bone implants.